2017
DOI: 10.1038/srep41776
|View full text |Cite
|
Sign up to set email alerts
|

Simvastatin suppresses the DNA replication licensing factor MCM7 and inhibits the growth of tamoxifen-resistant breast cancer cells

Abstract: Acquired tamoxifen resistance (TamR) remains a major challenge in breast cancer endocrine therapy. The mechanism of acquiring tamoxifen resistance remains elusive, and no effective drugs are available. In this investigation, we determined that the expression of the DNA damage marker γH2AX is upregulated under minichromosome maintenance protein 7 (MCM7) knockdown in phospho Ser807/811-retinoblastoma protein (p-Rb) defect cells. In addition, the expression of p-Rb was lower in TamR cells than in parental cells, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
57
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(65 citation statements)
references
References 38 publications
7
57
0
1
Order By: Relevance
“…The aim of the present study was to test the effects of simvastatin on the growth of human lipoma cells derived from tumors with heterozygous mutations or deletions of PTEN. Simvastatin was selected for use as it has been demonstrated to exert anti-proliferative and growth-inhibitory actions on a number of cancer cell lines and tumor animal models (6,7,10,18,22,(26)(27)(28)(29)(30). In accordance with these results, the present study demonstrated that simvastatin reduced the viability of PTEN mutant lipoma cells by inducing apoptosis in a time-and dose-dependent manner.…”
Section: Discussionsupporting
confidence: 83%
“…The aim of the present study was to test the effects of simvastatin on the growth of human lipoma cells derived from tumors with heterozygous mutations or deletions of PTEN. Simvastatin was selected for use as it has been demonstrated to exert anti-proliferative and growth-inhibitory actions on a number of cancer cell lines and tumor animal models (6,7,10,18,22,(26)(27)(28)(29)(30). In accordance with these results, the present study demonstrated that simvastatin reduced the viability of PTEN mutant lipoma cells by inducing apoptosis in a time-and dose-dependent manner.…”
Section: Discussionsupporting
confidence: 83%
“…Furthermore, it has been shown that the suppression of MCM proteins makes cells hypersensitive to DNA replication stresses through increased frequency of chromosome breaks (Ibarra et al, 2008). Recently, it was demonstrated that Simvastatin can downregulate MCM7, which led to increased DNA damage and cell death (Liang et al, 2017). It would be interesting to combine MCM reducing drugs, like Simvastatin, with other DNA damaging agents, to therapeutically treat CCNE1-amplified HGSOC patients.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, analyses have shown that in a molecular background where the tumor-suppressive retinoblastoma protein (pRb) axis is dysfunctional (eg, in SaOS2 osteosarcoma cells), the interference with the assembly of the minichromosome maintenance (MCM) complex and DNA replication causes more extensive DNA damages than in the presence of functional pRb (eg, in U2OS osteosarcoma cells). 42 Besides, premenopausal ER-positive breast cancer patients carrying a functional pRb are benefited from adjuvant tamoxifen treatment, in striking contrast to premenopausal ER-positive breast cancer patients with nonfunctional pRb, who do not experience any benefit. 43 Simvastatin negatively affects MCM7 expression, resulting in the elevation of the DNA damage marker, γH2AX.…”
Section: Introductionmentioning
confidence: 99%